206k views
2 votes
2(3x – _) = 6x + 8 Using the distributive property, what would go in the blank in order for the given statement to be correct? ​

2 Answers

2 votes

Answer:

2(3x - (-4)) = 6x + 8

Explanation:

2(3x - A) = 6x + 8

6x - 2A = 6x + 8

Equating constant terms on both sides :

-2A = 8

A = -4

Therefore, 2(3x - (-4)) = 6x + 8

User Liam Kernighan
by
4.9k points
5 votes

Answer:

Explanation:

2(3x-(-4))=6x+8

2*3x=6x

2*-(-4)=8

Negative times negative makes positive 4

User Peppe
by
4.7k points